Metagenomic next-generation sequencing shotgun for the diagnosis of infection in connective tissue diseases: A retrospective study - Wang, Huyan; Shi, Xiaowei; Yang, Huanhuan; Du, Yan; Xue, Jing (Frontiers in Cellular and Infection Microbiology, 2022)
Patients with connective tissue diseases (CTDs) are at high risk of infection due to various reasons. Identifying the pathogen quickly and accurately will contribute to decrease the morbidity and mortality. In this retrospective study, a total of 103 patients with CTDs admitted with suspected infection between December 2018 and September 2021 were assessed using metagenomic next-generation sequencing (mNGS) as well as conventional microbiological tests. Among these 103 patients, 65 were confirmed infection (Group I), 38 were excluded infection (Group II). mNGS reached a sensitivity of 90.77% in diagnosing pathogens in Group I. Besides, mNGS showed good performance in identifying mixed infection. In all infection types, lung infection was the most common. mNGS also played an important role in detecting Pneumocystis jirovecii, which was association with low CD4+ T cell counts inextricably. This study conveys that mNGS is a useful tool with promising diagnostic potential in identifying clinically relevant pathogens in patients with CTDs, which can guide the use of anti-infectious therapy better.